2011
DOI: 10.1289/ehp.1002255
|View full text |Cite
|
Sign up to set email alerts
|

Particulate Matter–Induced Health Effects: Who Is Susceptible?

Abstract: BackgroundEpidemiological, controlled human exposure, and toxicological studies have demonstrated a variety of health effects in response to particulate matter (PM) exposure with some of these studies indicating that populations with certain characteristics may be disproportionately affected.ObjectiveTo identify populations potentially at greatest risk for PM-related health effects, we evaluated epidemiological studies that examined various characteristics that may influence susceptibility, while using results… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

14
330
3
10

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 496 publications
(357 citation statements)
references
References 89 publications
14
330
3
10
Order By: Relevance
“…Although PM 2.5 components associated with primary combustion sources might be more toxic than others, our results suggest that fresh combustion particles also penetrate and persist indoors with a higher efficiency than secondary sulfate because of their smaller depositional losses. Low socioeconomic status, a predictor of susceptibility to PM-related health effects, 12 affects F because lowincome residences tend to have higher AER values and are more likely to live in close proximity to busy roadways. Our results suggest that both factors enhance exposure to ambient PM 2.5 .…”
Section: Implications For Epidemiologymentioning
confidence: 99%
See 2 more Smart Citations
“…Although PM 2.5 components associated with primary combustion sources might be more toxic than others, our results suggest that fresh combustion particles also penetrate and persist indoors with a higher efficiency than secondary sulfate because of their smaller depositional losses. Low socioeconomic status, a predictor of susceptibility to PM-related health effects, 12 affects F because lowincome residences tend to have higher AER values and are more likely to live in close proximity to busy roadways. Our results suggest that both factors enhance exposure to ambient PM 2.5 .…”
Section: Implications For Epidemiologymentioning
confidence: 99%
“…Low socioeconomic status has also been identified as a predictor of susceptibility to PMrelated health effects. 12 Various factors have been explored to explain this variability. Bell et al 5 concluded that as much as 37% of spatial and seasonal heterogeneity in relative risk of cardiovascular hospital admissions could be explained by variability in exposure to specific PM 2.5 species.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…PM 2.5 passes deep into the lung and has been shown to increase systemic inflammation, oxidative stress, and coagulation through PM 2.5 ‐mediated changes in the autonomic nervous system 11, 14. This has been linked to cardiovascular health impacts such as ischemic heart disease and cerebrovascular events such as ischemic stroke in the ambient air pollutant PM 2.5 literature 11, 15, 16, 17, 18. Other air pollutants in wildfire smoke have also been linked to cardiovascular and respiratory outcomes in urban and ambient air pollution studies, including nitrogen oxides, carbon monoxide, and ozone 7, 8, 9, 10…”
Section: Introductionmentioning
confidence: 99%
“…Children and older or chronically sick individuals are most susceptible to the negative effects of air pollution 9,10 . This finding is explained biologically by an immature or low immunological system response and particulate matter entering the respiratory system is expected to have a more acute respiratory effect in susceptible people 11 .…”
Section: Introductionmentioning
confidence: 99%